Emerging nanotechnologies in dentistry : processes, materials and applications - Subramani, Karthikeyan; Ahmed, Waqar (William Andrew, 2012)
New nanomaterials are leading to a range of emerging dental treatments that utilize more biomimetic materials that more closely duplicate natural tooth structure (or bone, in the case of implants). The use of nanostructures that will work in harmony with the body's own regenerative processes (eg, to restore tooth structure or alveolar bone) are moving into clinical practice. This book brings together an international team of experts from the fields of nanomaterials, biomedical engineering and dentistry, to cover the new materials and techniques with potential for use intra-orally or extra-orally for the restoration, fixation, replacement, or regeneration of hard and soft tissues in and about the oral cavity and craniofacial region. New dental nanotechnologies include the use of advanced inorganic and organic materials, smart and biomimetic materials, tissue engineering and drug delivery strategies. Book prepared by an interdisciplinary and international group of bio-nanomaterial scientists and dental/oral biomedical researchers Comprehensive professional reference for the subject covering materials fabrication and use of materials for all major diagnostic and therapeutic dental applications - repair, restoration, regeneration, implants and prevention. Book focuses in depth on the materials manufacturing processes involved with emphasis on pre-clinical and clinical applications, use and biocompatibility.